Semantic Web, Ontologies and Databases VLDB Workshop, SWDB-ODBIS 2007, Vienna, Austria, September 24, 2007, Revised Selected Papers - Christophides, Vassilis; Collard, Martine; Gutierrez, Claudio (Information Systems and Applications, incl. Internet/Web, and HCI, 2008)
This book constitutes the thoroughly refereed post-conference proceedings of the joint International Workshops on Semantic Web, Ontologies and Databases, SWDB-ODBIS 2007, co-located with the 33rd International Conference on Very Large Data Bases, VLDB 2007, held in Vienna, Austria, in September 2007. The 7 revised full papers presented together with 1 invited paper were carefully selected from 11 submissions. Among the topics addressed are semantics-aware data models and query languages; ontology-based views, mapping, transformations, and query reformulation; and storing and indexing semantic Web data and schemas.